Preparation of Curcumin-Liposomes using pH-Driven Method to Enhance Stability and Encapsulation Efficiency - Sekaringtyas, Fransiska Christydira; Purwajanti, Suwasmi; Mardliyati, Etik; Ningsih, Sri (Jurnal Kefarmasian Indonesia, 2020)
Curcumin, a hydrophobic polyphenol, derived from turmeric, has numerous pharmacological activities, including hepatoprotective, antioxidant, anti-inflammatory, antimicrobial, and anticarcinogenic. However, the therapeutic efficacy of curcumin is limited due to its poor oral bioavailability and high susceptibility to degradation. The poor oral bioavailability of curcumin has been attributed to its poor aqueous solubility and extensive first past metabolism. Curcumin dissolves in alkaline conditions but it is highly unstable undergoing rapid hydrolytic degradation in neutral or alkaline condition. To solve these problems, liposome-based encapsulation technology is applied to improve the bioavailability of curcumin. The existing method to prepare curcumin-liposome, thin-film method, is complex and usually required the use of organic solvents. In this study, pH-driven method, an organic solvent-free and easily encapsulation technique utilizing the pH-dependent solubility of curcumin was proposed to improve the stability and bioavailability. Curcumin-liposomes were prepared using phospholipon 90 H and soya lecithin as phospholipid sources. The characterizations of curcumin-liposomes include particle size, microstructure, encapsulation efficiency, infrared spectra, salt stability and storage stability. The particle size measured was 77.85 ± 0.39 nm. It was found that curcumin-liposomes prepared by the pH-driven method was stable during storage for 30 days and gave encapsulation efficiency of 60.71 ± 0.20%, higher as compared to the ones prepared by thin-film method. In conclusion, pH-driven is a promising method for the preparation of curcumin-liposomes to enhance stability and encapsulation efficiency